Examining the extent of youth participation in agricultural training program in Malete Youth Farm Kwara State - Ayinde, Latopa Abdul Lateef; Syed Abd Rashid, Sharifah Norazizan; Abu Samah, Asnarulkhadi; Abdullah, Haslinda (International Organization Of Scientific Research (IOSR), 2015)
Participation is a concept that has multi-dimensional meanings depending on the user. Youth participation in the same vein can be perceived according to the circumstance, the need, and the nature of the subject involved in the participation. Therefore, youth participation in agriculture training program in malete farm is a circumstantial idea designed to empower the youth in order to acquire some skills in agriculture business. This study examines the extent of youth participation in this program considering the prevailing socioeconomic condition of the youth and how the youth is involved in segments of the participation process. Using Malete youth Integrated Training Farm, qualitative case study method was employed for the study and the findings revealed that, there was a different degree of participation in the decision-making, implementation, sharing and evaluation. It appears that youth participate in the program as induced by the government through the monthly stipend and other motivational packages.